2019
DOI: 10.1007/s10899-019-09860-1
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Depiction of Statistical Information Improves Gambling-Related Judgments

Abstract: The domain of gambling is rife with both diagnostic and non-diagnostic information. Previous studies examining scratch card gambling have demonstrated that people are often biased by intuitively appealing, yet non-diagnostic information (i.e., unclaimed prize information). The current study investigated how varying the presentation format of a diagnostic piece of information (i.e., payback percentage) could influence participants’ use of this information when in conflict with unclaimed prize information. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
(39 reference statements)
2
33
0
Order By: Relevance
“…Throughout the study, participants were asked to make various gambling-related judgments regarding presented scratch card games. All measures used were adopted from Walker et al (2018Walker et al ( , 2019.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the study, participants were asked to make various gambling-related judgments regarding presented scratch card games. All measures used were adopted from Walker et al (2018Walker et al ( , 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Within the domain of scratch card gambling, non-diagnostic (i.e. information that does not aid in assessing the true value of a card) unclaimed prize information has been shown to bias scratch card choices (Walker et al, 2019(Walker et al, , 2018. Unclaimed prize information refers to the number of prizes still available to be won and is made widely available in many jurisdictions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were 8 information aid studies (33%) suggesting that information aids had a favorable responsible gambling impact. For example , Walker, Stange, Dixon, Koehler, and Fugelsang (2019) found that when scratch card players had access to both the number of unclaimed prizes left and the payback percentage (the ratio of unclaimed prizes to total scratch cards remaining) in a numerical format, participants were influenced by the former even though it is only the latter that is diagnostic. In a follow-up experiment, Walker et al (2019) presented the same payback percentage information using a visual (a five-star rating system).…”
Section: Information Aidsmentioning
confidence: 99%
“…For example , Walker, Stange, Dixon, Koehler, and Fugelsang (2019) found that when scratch card players had access to both the number of unclaimed prizes left and the payback percentage (the ratio of unclaimed prizes to total scratch cards remaining) in a numerical format, participants were influenced by the former even though it is only the latter that is diagnostic. In a follow-up experiment, Walker et al (2019) presented the same payback percentage information using a visual (a five-star rating system). Participants now more often relied on the payback percentage to make decisions about scratch cards, even though they did not understand the concept of payback percentage any better than participants in the first experiment.…”
Section: Information Aidsmentioning
confidence: 99%